Tailored p‐Orbital Delocalization by Diatomic Pt‐Ce Induced Interlayer Spacing Engineering for Highly‐Efficient Ammonia Electrosynthesis (Adv. Energy Mater. 6/2023). Issue 6 (11th February 2023) - Chen, Dong; Zhang, Shaoce; Yin, Di; Li, Wanpeng; Bu, Xiuming; Quan, Quan; Lai, Zhengxun; Wang, Wei; Meng, You; Liu, Chuntai; Yip, SenPo; Chen, Fu‐Rong; et al.
Abstract : Electrochemical Nitrate Reduction In article number 2203201, Johnny C. Ho and co‐workers design 2D SnS nanosheets with tailored interlayer spacing, including both expansion and compression, through active diatomic Pt‐Ce pairs. The tailored interlayer spacing tunes the delocalized electron density of localized p‐orbitals in Sn and changes chemical affinity towards NO3 − and NO2 −, realizing an excellent ammonia Faradaic efficiency and yield rate from the electrochemical nitrate reduction.